Considerations for Summer Online Book Clubs. (26th September 2018) - Smith, Jennifer M.
Abstract: Middle school students participated in a summer online book club as an opportunity to read and discuss texts during the summer months. The author provides considerations for educators who may be interested in conducting summer online book clubs with their students, based on student interviews and observations throughout the summer book club.